Who Cares? Perception of Loneliness in Patients Treated for Coronary Heart Disease - Mitti Blakoe; Selina Kikkenborg Berg; Ida Elisabeth Højskov; Pernille Palm; Camilla Bernild (SAGE Publishing, 2022)
Social support is known to be essential to cope with the physical and psychological aftermath following coronary heart disease treatment. Consequently, patients experiencing loneliness may be placed in a vulnerable situation. The aim of this study was to provide insight into the nuances and complexity of loneliness and its impact on health behaviour in the early rehabilitation period following treatment. The study used a hermeneutic philosophical approach. Patients classified as lonely were interviewed in either a focus group ( n = 7) or in an individual interview ( n = 10). We analysed the empirical material using inductive content analysis. The analysis illuminated various dimensions of patients' perceived loneliness; 'Loneliness as an emotional pain', 'A changed, but unmet need for social support' and 'Striving for symmetry in relationships'. Loneliness negatively influenced patients' ability to adapt to the critical event and manage health behaviour changes. Insight into the mechanisms that aggravate loneliness may inform future social support interventions.